Social Stratification of Jerusalem Society during the Crusades (1174–1185) as Represented in the Film Kingdom of Heaven - Andhika Issam Pratama; Febri Priyoyudanto (Universitas Islam Negeri Sumatera Utara, 2026)
This study critically examines the configuration of social stratification in Jerusalem during the period 1174–1185 as represented in the film Kingdom of Heaven. Employing a qualitative methodological framework, the research integrates content analysis and narrative analysis to systematically identify hierarchical structures depicted within the film, including the monarchy, nobility, military aristocracy, urban classes, and non Latin communities. These cinematic representations are subsequently juxtaposed with contemporary historiographical scholarship to evaluate their representational accuracy and interpretive deviations. The findings indicate that, although the film incorporates narrative simplifications and dramatization, it retains the fundamental characteristics of socio-political inequality in the Latin Kingdom particularly the dominance of the Frankish elite, restricted mobility among lower strata, and the interplay of religious authority and political power in sustaining hierarchical order. The study concludes that film functions not merely as a medium of entertainment but as a cultural apparatus capable of shaping public perceptions of medieval societies through selective reconstruction of the past.